2015
DOI: 10.7763/jocet.2015.v3.190
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Photovoltaic String with Compound Parabolic Concentrator

Abstract: Abstract-Photovoltaic (PV) system is used to directly converting the solar energy into the electrical energy. Compound Parabolic Concentrator (CPC) is a non-imaging concentrator which is considered in this study for reducing the cost of electrical energy. Two configurations are numerically studied namely one with simple typical flat PV string and the other PV string with CPC. The truncated CPC with concentration ratio of 2.3 and an acceptance angle of 41.75° is considered in the analysis of PV string with CPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ali and Gandhidasan theoretically compared the electrical performance of a PV module with and without the CPC (2.3×) and found that the electrical power of the PV module increased to about 35% when the CPC was used. However, they observed a decrease in the electrical power output due to rise in operating cell temperature.…”
Section: Studies In the Literature On The Application Of Cpcs To Photmentioning
confidence: 99%
“…Ali and Gandhidasan theoretically compared the electrical performance of a PV module with and without the CPC (2.3×) and found that the electrical power of the PV module increased to about 35% when the CPC was used. However, they observed a decrease in the electrical power output due to rise in operating cell temperature.…”
Section: Studies In the Literature On The Application Of Cpcs To Photmentioning
confidence: 99%
“…Low concentration methods include compound parabolic concentrators (Schuetz et al, 2011;Sellami and Mallick, 2013;Ali and Gandhidasan, 2015), V-trough concentrators (Tang and Liu, 2011;Tina and Scandurra, 2012;Bahaidarah et al, 2015) or flat planar concentrators also known as boosters (Tanaka, 2011;Andrews et al, 2011;Pavlović, 2015). In particular, the flat planar concentrators have the advantages of being inexpensive compared to both V-trough and parabolic reflectors (Andrews et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…In this context, the evaluation of the real increase of yearly energy produced by a LCPV requires a detailed model of the system, especially for the electrical aspects. Different aspects of the modeling of LCPVs has been recently investigated and discussed by many researchers (Yadav et al, 2014;Palaskar and Deshmukh, 2014;Ali and Gandhidasan, 2015;Tang and Liu, 2011;Bahaidarah et al, 2015;Tanaka, 2011;Andrews et al, 2011;Pavlović, 2015;Rö nnelid et al, 2000;Alboteanu et al, 2015).…”
Section: Introductionmentioning
confidence: 98%